Changes to white matter microstructure in transient ischemic attack: A longitudinal diffusion tensor imaging study. Issue 11 (16th August 2017) - Ferris, Jennifer K.; Edwards, Jodi D.; Ma, Jennifer A.; Boyd, Lara A.
Abstract: Transient ischemic attack (TIA) is associated with localized ischemic changes, identifiable by diffusion‐weighted imaging. Past research has not considered whether TIA is also associated with diffuse changes to white matter microstructure; further past work has not tracked changes longitudinally. Here we examine whole‐brain changes in fractional anisotropy (FA) in individuals with TIA presenting with sensorimotor symptoms. Twenty individuals with a recent (within 30 days) TIA and 12 healthy older adults were recruited. Participants underwent 3.0 T diffusion MRI at baseline; scans were repeated for the TIA group 90 days post‐TIA. Track‐based spatial statistics (TBSS) was used to conduct a voxel‐wise analysis of FA between groups. FA was significantly lower in the TIA group relative to healthy controls, primarily in anterior white matter tracts including: forceps minor, anterior thalamic radiations, cingulum, inferior fronto‐occipital fasciculus, and corticospinal tract. TBSS results informed an ROI‐based longitudinal examination of FA in the TIA group. There were no changes to TBSS‐identified clusters, forceps minor, or the corticospinal tract over time. There was lower FA in the anterior thalamic radiations in the TIA‐affected hemisphere at baseline, but no difference between hemispheres at 90 days. In summary, individuals with TIA presenting with sensorimotor symptoms have decreased FA in tracts that are also implicated in sensorimotor function, which outlast the clinical symptoms associated with TIA. This suggests a more profound type of brain damage associated with TIA than has been typically described in past work. Diffusion tensor imaging may have utility as a marker of TIA‐associated changes to white matter pathways. Hum Brain Mapp 38:5795–5803, 2017 . ©2017 Wiley Periodicals, Inc.